THE CASE OF ISLAMIC LEADERSS - Ishomuddin, Ishomuddin (Jurnal Bestari, 1992)
Recently, there are three kinds of ideologies or tendencies in moslems. It is ispecially yhe relationship between Islam and governmenttal. First, ideolology illustrates that islam is not merely religion as western interprete, that is only involves relationship between manking and god(Allah)